Body Image, Diet Behavior and Self-Welfare of Self- Pride - Sugandi,; Ade Fyandra,; Valda Anadiya Stia,; Putri Arissah Harapan Oppo, (Technium Social Sciences Journal, 2021)
This study aims to determine the effect of body image, dietary behaviour, and self-welfare on self-esteem in students of FISIP Mulawarman University using a quantitative approach. The subjects of this study were 110 respondents who were selected using the technique probability sampling with method simple random sampling. The collected data were analyzed by using SPSS 25.0 for the Windows program. This study indicates an influence between body image, dietary behaviour, and self-welfare on self-esteem. There is an influence between body image on self-esteem. There is an influence between dietary behavior on self-esteem. There is an effect of self-welfare on self-esteem.